Pemberdayaan Masyarakat dalam Kesiapsiagaan Bencana di Komunitas Melalui Optimalisasi Pelaku Wisata Berbasis Tourism Health Nursing - Januarti, Luluk; Yulianto, Sofi (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2025)
Community preparedness for disasters and emergencies is an essential component in reducing morbidity and mortality. This community service program aimed to empower the community in emergency response through optimizing the role of tourism actors based on Tourism Health Nursing in Versel Village, Pasean District. The methods implemented included socialization, risk screening, the establishment of health cadres, the development of an emergency response handbook, creation of health education media, as well as training and simulation activities. The training covered topics such as recognizing emergency conditions, management of cardiac arrest and respiratory failure, choking, first aid (P3K), utilization of household materials in emergency response, management of febrile seizures, and stress management. The results showed a significant improvement in cadres’ understanding, where prior to education, training, and simulation, most participants (60%) had low comprehension, while after the intervention, almost all (90%) demonstrated good understanding. These findings indicate that the program successfully enhanced the capacity and preparedness of the community—particularly health cadres—in managing emergencies and disasters within the tourism-based community environment.